Sexual and reproductive health issues facing Southeast Asian beer promoters: a qualitative pilot study - Webber, Gail C.; Spitzer, Denise L (Université d'Ottawa | University of Ottawa, 2010)
Background - In Southeast Asia, hundreds of thousands of young rural women migrate from their villages to the larger cities in search of work. Many find employment with beer companies or in the clubs where beer is sold, promoting the sale of beer. Previous research suggests these young migrants are in a highly vulnerable position. This paper will describe the findings of an October 2009 meeting to develop a research agenda on the sexual and reproductive health of beer promoters and a subsequent pilot study of focus groups with beer promoters to review this agenda. // Methods - Participants of the research meeting representing beer promoters, academics, non-governmental organizations (NGOs), government and the beer industry from Cambodia, Thailand, Laos, and Vietnam collaborated in the development of three key research themes. The themes were verified in focus group discussions with beer promoters organized by local research partners in all four countries. The focus group participants were asked what they felt were the key sexual and reproductive health issues facing them in a non-directive and unstructured manner, and then asked to comment more specifically on the research priorities developed at the meeting. The focus groups were recorded digitally, transcribed, and translated into English. The data were analyzed by coding for common themes and then developing matrices to compare themes between groups. // Results - The participants of the meeting identified three key research themes: occupational health (including harassment and violence, working conditions, and fair pay), gender and social norms (focusing on the impact of power relations between the genders on women's health), and reproductive health (knowledge and access to reproductive health care services). The participants in the focus groups in all four countries agreed that these were key priorities for them, though the emphasis on the most important issues varied between groups of women. Sexual harassment in the workplace and challenges in accessing reproductive health care services because of the barriers of cost, shyness, and stigmatizing attitudes of health care providers were common problems for many of the women. // Conclusions - There is a need for regional research and programming for beer promotion women in Southeast Asia focusing on the three research themes of occupational health, gender norms and reproductive health. Such research and programs could provide important benefits for many beer promotion women who currently face significant risks to their sexual and reproductive health.